Strategic Alliances Between a NHS Foundation Trust and the UK Pharmaceutical Industry - Hill, Russell (2007)
Inter-organisational relationships have been considered an important tool in seeking to develop a competitive advantage. The Department of Health and Association of the British Pharmaceutical Industry have proposed a long-term leadership strategy calling for greater partnership working between the NHS and the pharmaceutical industry. This management project seeks to consider the risks, benefits, barriers, enablers and potential opportunities for partnership working between four global pharmaceutical companies and a mental health NHS Foundation Trust.